Effect of Endotoxemia in Suckling Rats on Pancreatic Integrity and Exocrine Function in Adults: A Review Report - Jolanta Jaworek; Barbara Tudek; Paweł Kowalczyk; Michalina Kot; Joanna Szklarczyk; Anna Leja-Szpak; Piotr Pierzchalski; Joanna Bonior; Artur Dembiński; Piotr Ceranowicz; Zygmunt Warzecha; Katarzyna Nawrot-Porąbka; et al. (Gastroenterology Research and Practice)
Background. Endotoxin (LPS), the component of Gram-negative bacteria, is responsible for sepsis and neonatal mortality, but low concentrations of LPS produced tissue protection in experimental studies. The effects of LPS applied to the suckling rats on the pancreas of adult animals have not been previously explored. We present the impact of neonatal endotoxemia on the pancreatic exocrine function and on the acute pancreatitis which has been investigated in the adult animals. Endotoxemia was induced in suckling rats by intraperitoneal application of LPS from Escherichia coli or Salmonella typhi. In the adult rats, pretreated in the early period of life with LPS, histological manifestations of acute pancreatitis have been reduced. Pancreatic weight and plasma lipase activity were decreased, and SOD concentration was reversed and accompanied by a significant reduction of lipid peroxidation products (MDA + 4 HNE) in the pancreatic tissue. In the pancreatic acini, the significant increases in protein signals for toll-like receptor 4 and for heat shock protein 60 were found. Signal for the CCK1 receptor was reduced and pancreatic secretory responses to caerulein were diminished, whereas basal enzyme secretion was unaffected. These pioneer studies have shown that exposition of suckling rats to endotoxin has an impact on the pancreas in the adult organism.